2022
DOI: 10.3389/fcell.2022.890121
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neddylation and Immune Response

Abstract: Neddylation is a ubiquitin-like post-translational protein modification. It occurs via the activation of the neural precursor cell expressed, developmentally downregulated protein 8 (NEDD8) by three enzymes: activating enzyme, conjugating enzyme, and ligase. NEDD8 was first isolated from the mouse brain in 1992 and was initially considered important for the development and differentiation of the central nervous system. Previously, the downregulation of neddylation was associated with some human diseases, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…By screening the protein–protein interaction networks, we found that NEDD8 might serve as a potential target of FBXO11. NEDD8 is characterized as a type of posttranslational protein modification that binds to the target protein via a process similar to ubiquitination 44 . Both IRF3 and IRF7 served as potential substrates of neddylation during virus infection and can inspire antiviral responses 44 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By screening the protein–protein interaction networks, we found that NEDD8 might serve as a potential target of FBXO11. NEDD8 is characterized as a type of posttranslational protein modification that binds to the target protein via a process similar to ubiquitination 44 . Both IRF3 and IRF7 served as potential substrates of neddylation during virus infection and can inspire antiviral responses 44 .…”
Section: Discussionmentioning
confidence: 99%
“…NEDD8 is characterized as a type of posttranslational protein modification that binds to the target protein via a process similar to ubiquitination 44 . Both IRF3 and IRF7 served as potential substrates of neddylation during virus infection and can inspire antiviral responses 44 . NEDD8 directly targets the C‐terminal lysine residues of IRF7 and enhances its transcription by promoting IFN‐I signaling after infection with the SeV virus 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1453 At present, the primary approach to studying the neddylation pathway involves interfering with the expression of particular genes through siRNA or inhibiting the activation enzyme NAE using small molecule inhibitors such as MLN4924 which deactivate the entire neddylation pathway. 1454 The formation of a stable covalent bond with NEDD8 and competitive inhibition of NAE's activation of NEDD8 leads to inhibition of the neddylation pathway and partially blocks the ubiquitination pathway dependent on CRL. This inhibition results in the accumulation of substrates, triggering various cellular responses, such as cell cycle arrest, apoptosis, aging, and autophagy.…”
Section: Other Modificationsmentioning
confidence: 99%
“…Many recent studies have shown that NEDD8 or enzymes related to the neddylation pathway are overexpressed in various cancers, including lung cancer, 1451 liver cancer, 1452 CRC, 1449 and esophageal squamous cell carcinoma 1453 . At present, the primary approach to studying the neddylation pathway involves interfering with the expression of particular genes through siRNA or inhibiting the activation enzyme NAE using small molecule inhibitors such as MLN4924 which deactivate the entire neddylation pathway 1454 . The formation of a stable covalent bond with NEDD8 and competitive inhibition of NAE's activation of NEDD8 leads to inhibition of the neddylation pathway and partially blocks the ubiquitination pathway dependent on CRL.…”
Section: Other Modificationsmentioning
confidence: 99%